2022
DOI: 10.3390/vaccines10081355
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Psychological Factors and Vaccine Conspiracy Beliefs in Influenza Vaccine Hesitancy and Uptake among Jordanian Healthcare Workers during the COVID-19 Pandemic

Abstract: Vaccination to prevent influenza virus infection and to lessen its severity is recommended among healthcare workers (HCWs). Health professionals have a higher risk of exposure to viruses and could transmit the influenza virus to vulnerable patients who are prone to severe disease and mortality. The aim of the current study was to evaluate the levels of influenza vaccine acceptance and uptake as well as its determinants, among Jordanian HCWs over the last influenza season of 2021/2022. This study was based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 118 publications
5
44
0
Order By: Relevance
“…Therefore, paying for vaccines in general, including the booster doses of COVID-19 vaccines, can be a major hurdle to the efforts aimed to promote vaccination. Consistent with this observation, several previous studies showed a similar lower rate of vaccine acceptance if payment was needed in the context of COVID-19 [18,35], HPV [36], and influenza vaccination [37].…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, paying for vaccines in general, including the booster doses of COVID-19 vaccines, can be a major hurdle to the efforts aimed to promote vaccination. Consistent with this observation, several previous studies showed a similar lower rate of vaccine acceptance if payment was needed in the context of COVID-19 [18,35], HPV [36], and influenza vaccination [37].…”
Section: Discussionsupporting
confidence: 81%
“…Nurses’ attitudes towards influenza vaccination for 2022–2023 are important since the past two seasons have seen historically low levels of influenza and an increase in influenza activity is expected. Before this study, only Sallam et al [ 22 ] had measured the intentions of healthcare workers, including nurses, to accept influenza vaccination (for 2021–2022), and they found that the acceptance rates were highest among males, physicians, dentists, and healthcare workers with high confidence in the vaccine and a strong sense that it was part of their collective responsibility to get vaccinated. To test whether the same would be found, we estimated the levels of influenza vaccine acceptance, as well as its determinants, among nurses in Greece for the2022/2023 season.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed significant vaccine hesitancy in the United States and Canada [ 7 ]. In previous studies using the vaccine hesitancy model, researchers have typically focused on the trust in vaccines, such as the trust in their safety and efficacy [ 7 , 8 , 9 ]. The current study presented a different picture of vaccine hesitancy in India; people’s perceptions of the COVID-19 vaccine are favorable, and vaccine hesitancy has not been widespread.…”
Section: Discussionmentioning
confidence: 99%
“…In 1985, the Indian government added the measles vaccine under the Universal Immunization Programme (UIP) launch. The scale was established by combining the questionnaire proposed by the WHO in 2015 with a questionnaire from a related study [ 8 , 9 ]. The scale of the trust in the social environment displayed good reliability as reflected by a Cronbach’s α = 0.696.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation